2018
DOI: 10.1016/j.solener.2018.02.053
|View full text |Cite
|
Sign up to set email alerts
|

Design, construction, and operation of the first industrial salinity-gradient solar pond in Europe: An efficiency analysis perspective

Abstract: 17A 500 m 2 industrial salinity-gradient solar pond (SGSP) was constructed in a mineral processing 18 plant (Solvay Minerales) in Granada (Spain). This renewable energy technology was designed to 19 supply a low-temperature heat (up to 60 ºC) to achieve the temperature requirements of the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 42 publications
(3 reference statements)
0
11
0
Order By: Relevance
“…The solar pond in Granada started its operation in July 2014 as was described by Alcaraz et al (2018a).…”
Section: Evolution Of the Salinity Gradient In The Granada Solar Pondmentioning
confidence: 99%
“…The solar pond in Granada started its operation in July 2014 as was described by Alcaraz et al (2018a).…”
Section: Evolution Of the Salinity Gradient In The Granada Solar Pondmentioning
confidence: 99%
“…A Scientometric Approach to Analyze Scientific Development on Renewable Energy Sources http://www.jdis.org https://www.degruyter.com/view/j/jdis with 16 papers on the subjects of exergetic analysis and assessment of different systems (Granovskii, Dincer, & Rosen, 2007;Hacatoglu, Dincer, & Rosen, 2011;Khalid, Dincer, & Rosen, 2015;Rezaie, Reddy, & Rosen, 2018), hybrid renewable energy systems for different applications (Krajačić et al, 2018;Maleki, Rosen, & Pourfayaz, 2017;Soltani et al, 2014;Zhang et al, 2018), and others researches on similar subjects. Akbarzadeh has 10 papers on the subject, almost all about salinitygradient solar ponds related to electric power generation (Akbarzadeh, Johnson, & Singh, 2009;Alcaraz et al, 2018;Bernad et al, 2013;Leblanc, Andrews, & Akbarzadeh, 2010;Singh et al, 2017;Singh, Tundee, & Akbarzadeh, 2011;Valderrama et al, 2011). Kroposki and his network are linked with the network of Hodge.…”
Section: Journal Of Data and Information Sciencementioning
confidence: 99%
“…Similar successful industrial applications have been reported from other parts of the globe. For example, reaching up to 90 °C in a flotation cell using an annual solar insolation of 1600 kWh/m 2 in Granada, Spain (Alcaraz et al, 2018) and achieving an average air tem-perature of 40 °C utilizing an annual solar insolation of 1500 kWh/m 2 in Victoria, Australia (Bawahab et al 2019). Figure 2 provides the global distribution of SGSP projects.…”
Section: Practical Logisticsmentioning
confidence: 99%